The Supply Chain Integration, and Product Modularity as Antecedents of the Market Valuation of Firms in Thai Solar Industry - Somjai, Sudawan; Hannarkin, Piyapan; Pokmontree, Avasada; Vipaporn, Tanapon (International Journal of Supply Chain Management, 2020)
The main purpose of the current study is to examine the supply chain integration, and product modularity as antecedents of the market valuation. The study is carried out on the supply chain of the solar industry of Thailand. The reason why the solar industry is chosen is that the greater emphasis on rising oil prices, global regulatory environment, and climate change resulted in increased adoption of clean technology processes. Over the next few decades, the solar energy would be considered as an important technology stemming from fast-paced innovation and huge technological investment. Being an infant industry, the solar energy supply chain is evolving rapidly with the entrance of new as well as already established firms. The study has used the SEM-PLS to analyses the data gathered from the firms in the solar industry. The findings of the study argue that the aggregated product modularity affects the supply chain flexibility and supply chain’s ability of delivering product variety, across the supply chain. Such aggregated product modularity, being an important SC construct, shows the product modularity of supply chain as a whole.